Efeitos da rodovia na atividade de Salvator merianae (Duméril & Bibron, 1839) - Rocha, Tomas de Lima (2021)
Highways are one of the biggest responsibles of terrestrial biodiversity loss. Amongst highway impacts on fauna there are mainly the roadkilling, the barrier effect, isolating populations, and the edge effect zone on habitat quality, which influences on the distribution of populations. In general, road ecology studies indicate that road effects on reptiles are negative, but most of them evaluated the problems related to roadkilling, meanwhile few evaluated the other effects. This study aims to understand how a highway affects the population of the tegu lizard Salvator merianae in a protected area in the Atlantic Forest of southeastern Brazil. Tegu is a large-sized lizard widely distributed in South America, commonly found near anthropized environments in search of food and places for thermal regulation. One of these environments are roads and highways, where individuals are in risk of being run over. The study area corresponds to a small part of the federal highway BR-101, one of the busiest in the country, inside the Sooretama Biological Reserve, Espírito Santo. In addition to evaluating the roadkilling of tegus, this work focused on understanding the effects of the road on the activities, distribution and its movement around the road environment. With the use of camera traps, we found out that tegus are positively related to road proximity and high temperatures, which raises its detectability. In addition, daily activity hours of tegus near BR-101 were longer than those found more distant from the highway. These results are probably related to the higher light incidence and heat that raise the temperature in the environment at the road edge, which attract tegus and allow them to become active earlier. Rate of tegus crossing the highway through drainage manholes was 16%. Most records of individuals close to the passages were not those animals crossing the highway. From the total of 47 individuals captured and tagged, 11 were recaptured. The displacement of individuals from capture to recapture took place over short distances of up to 1000 meters. None individuals were recaptured on opposite sides of the highway, which can be explained by the size of the home range and territorial habit of the tegu. None of the tegus that were accompanied with the spool of thread (N= 14 individuals) moved towards the highway. However, some tegus were recorded roadkilled, before and during this study, seven and six, respectively, although none of them were among those previously marked in this study. The proximity of tegus to the busy highway is harmful, as individuals can be at the risk of being roadkilled, hunted and chased by people. These same individuals keep their home range very close to the highway, due to favorable habitat conditions, but the rolling lane can act as a barrier for populations on both sides of the highway, as few individuals actually cross the highway. The proximity of the highway has a positive effect on the distribution of tegu, but it has negative effects on its movement, and it can also have negative effects on the population gene flow.